PETER HALL - Good Cities, Better Lives (2014) - Monclús, Javier (ZARCH, 2015)
PETER HALL (with contributions from Nicholas Falk)Good Cities, Better Lives: How Europe Discovered the Lost Art of Urbanism Routledge, Londres, 2013, 366 p. InglésISBN: 978-0-415-84022-4